5-HT1B receptor augmented 5-HT vasoconstrictor response of pulmonary artery in monocrotaline-induced pulmonary hypertensive rats - Wang Huai-Liang; Dong Xu; Zhang Xin-Hua; Xing Jun (Acta Pharmacologica Sinica; Vol 22, No 3 (March 2001): Acta Pharmacologica Sinica, 2016)
Aim: To study the relationship between the vasoconstrictor effect to 5-hydroxytryptamine (5-HT) and the expression of 5-HT1B-and 5-HT1D)-receptors in pulmonary arteries (PA) from normal and pulmonary hypertensive (PHT) rats. Methods: Monocrotaline (MCT)-treated rats were used as a model for chronic PHT. Concentration-response curves of 5-HT induced pulmonary vasoconstriction were established and semiquantitative RT-PCR was performed to identify mRNA expression of 5-HT1B- and 5-HT1D-receptors in rat PA. Results: 5-HT induced vasoconstrictor response of PA from MCT rats was enhanced (Emax) 50 % +/- 20 % vs control 38 % +/- 21 %, P < 0.05). A significantly higher level of 5 -HT1B receptor mRNA expression was detected in PA from MCT rats. The ratio of the PCR products of 5-HT1B receptor gene to those of beta-actin gene was much higher in MCT rats than that in control rats (0.43 +/- 0.14 vs control 0.27 +/- 0.15, P < 0.05). Conclusion: 5-HT1B receptor is involved in pulmonary vasoconstriction and the enhanced level of 5-HT1B receptor mRNA expression is closely related to the augmentation of 5-HT induced pulmonary vasoconstriction in PHT rats.